MiR-33a is a therapeutic target in SPG4-related hereditary spastic paraplegia human neurons. (22nd February 2019) - Nakazeki, Fumiko; Tsuge, Itaru; Horie, Takahiro; Imamura, Keiko; Tsukita, Kayoko; Hotta, Akitsu; Baba, Osamu; Kuwabara, Yasuhide; Nishino, Tomohiro; Nakao, Tetsushi; Nishiga, Masataka; Nishi, Hitoo; et al.
Abstract : Recent reports, including ours, have indicated that microRNA (miR)-33 located within the intron of sterol regulatory element binding protein (SREBP) 2 controls cholesterol homeostasis and can be a potential therapeutic target for the treatment of atherosclerosis. Here, we show that SPAST, which encodes a microtubule-severing protein called SPASTIN, was a novel target gene of miR-33 in human. Actually, the miR-33 binding site in the SPAST 3′-UTR is conserved not in mice but in mid to large mammals, and it is impossible to clarify the role of miR-33 on SPAST in mice. We demonstrated that inhibition of miR-33a, a major form of miR-33 in human neurons, via locked nucleic acid (LNA)-anti-miR ameliorated the pathological phenotype in hereditary spastic paraplegia (HSP)-SPG4 patient induced pluripotent stem cell (iPSC)-derived cortical neurons. Thus, miR-33a can be a potential therapeutic target for the treatment of HSP-SPG4.